Pengaruh Profesionalisme Badan Pengawas, Moralitas Individu, Kesesuaian Kompensasi dan Komitmen Organisasi Terhadap Kecenderungan Kecurangan Akuntansi (Studi Empiris Pada LPD Se-Kecamatan Mengwi, Kabupaten Badung) - Ni Made Dessy Natalia; I Made Wianto Putra; Luh Kade Datrini (Jurnal Riset Akuntansi Warmadewa, 2020)
This study entitled "The Effect of Professionalism of the Supervisory Body, Individual Morality, Compensation Suitability and Organizational Commitment to the Tendency of Accounting Fraud (Empirical Study at LPDs in Mengwi District, Badung Regency), which aims to test empirically the effect of each variable, namely the Professionalism of the Supervisory Body. Individual Morality, Compensation Compensation and Organizational Commitment to Accounting Fraud Tendencies. The samples were determined by using purposive sampling method. The population in this study were 38 LPDs in Mengwi District, Badung Regency with a sample of 152 respondents. The method of analysis in this study is multiple linear regression analysis, with the form of the regression equation obtained Y = 53.015 - 0.245X1 - 0.211X2 - 0.213X3 - 0.273X4, which means that all regression coefficients affect the dependent variable (Y). The results of data analysis indicate that the professionalism of the supervisory body, individual morality, suitability of compensation and organizational commitment have a negative effect on the tendency of accounting fraud in LPDs in Mengwi District, Badung Regency.